2015
DOI: 10.5860/rusq.54n3.12
|View full text |Cite
|
Sign up to set email alerts
|

Management: From Infancy to Adolescence: Seven Lessons for Creating a Sustainable Graduate Student Orientation Program

Abstract: In recent years, academic librarians have been strengthening the suite of orientation opportunities they offer students and placing a priority on familiarizing them with collections and services to support their academic endeavor. At most universities, the primary-if not the exclusive-target of these efforts is the undergraduate population. Yet graduate students also need a thorough orientation to their postgraduate environment and what the library has to offer. But for a variety of reasons, that audience can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Graduate students have indicated that meeting with their faculty advisor prior to the beginning of classes was valuable in preparing for their academic and professional responsibilities (Taub & Komives, 1998). Academic librarian Harriet Lightman (2015) shared programming focused on acculturating graduate students to the resources and practices of research, which included opportunities for students to interact with peers, faculty, and administrators.…”
Section: Academic Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Graduate students have indicated that meeting with their faculty advisor prior to the beginning of classes was valuable in preparing for their academic and professional responsibilities (Taub & Komives, 1998). Academic librarian Harriet Lightman (2015) shared programming focused on acculturating graduate students to the resources and practices of research, which included opportunities for students to interact with peers, faculty, and administrators.…”
Section: Academic Acculturationmentioning
confidence: 99%
“…Grounded in the context of socialization, GSOP initiates a process of dual enculturation into students' individual academic sphere and the broader institutional community (Poock, 2006). GSOP is easily thought of as characterizing a deeper focus on developing students into academics and researchers (e.g., Lightman, 2015), while orientation at the undergraduate level can be seen as introducing job preparation or career exploration more broadly. Despite the more academic emphasis, GSOP can address the cocurricular, intersectional needs of the various graduate student demographics through multiple facets of programming (Poock, 2006;Rapp & Golde, 2008).…”
mentioning
confidence: 99%
“…The existing literature includes several reports that focus on the onboarding and orientation of graduate students [2][3][4][5][6]. These reports target the orientation of graduate students at the university, college, and/or department levels [2][3][4][5] or the onboarding of graduate students in research groups [6].…”
Section: Existing Literature and Contributions Of This Report To The Latter 21 Graduate Student Onboarding And Orientationmentioning
confidence: 99%
“…The existing literature includes several reports that focus on the onboarding and orientation of graduate students [2][3][4][5][6]. These reports target the orientation of graduate students at the university, college, and/or department levels [2][3][4][5] or the onboarding of graduate students in research groups [6]. Notably, these publications discuss a number of best practices and make several recommendations vis-à-vis graduate student orientation and onboarding efforts.…”
Section: Existing Literature and Contributions Of This Report To The Latter 21 Graduate Student Onboarding And Orientationmentioning
confidence: 99%